The recognition of Youth and Adult Education specificities: constitution and organization of YAE programs - Soares, Leoncio José Gomes; Soares, Rafaela Carla e Silva (Education Policy Analysis Archives, 2014)
This article aims to discuss the specificities of Youth and Adult Education that are present in three programs designed for this public developed in different Brazilian regions. These programs were selected for the qualitative research amid 63 others identified in a survey done in higher education institutions, they are: Zé Peão Project (Paraíba), Paranoá Project (Distrito Federal), and Ensino Fundamental para Jovens e Adultos Project (Minas Gerais). Some criteria were used to select the programs: time of existence, tradition, history, and community impacts. The data was collected through the visit to the programs and by interviews with students and former students, educators and coordinators. The analysis shows that some YAE specificities are recurrent among the programs: the popular education legacy deeply stressed in the curricula; the student’s diversity; the variety of teaching resources; the teacher education designed for young and adult people; and the permanent struggle toward public policies for the YAE field.